Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 4 Medan - Zulmawati Zulmawati; Dian Mulriani (Journal on Education, 2023)
This study aims to analyze: differences in the effect of the Problem Based Learning model and the Direct Learning model on student learning outcomes; This research is a quantitative research with a quasi-experimental design type. The population in this study were all class VIII students of SMP Negeri 4 Medan for the 2022/2023 academic year. Testing was carried out using Two Way ANOVA. The results of the study show that (1) there are differences in the effect of the problem-based learning model and the direct learning model on student social studies learning outcomes; there is no interaction between social studies initial skills (high, medium, and low) and learning models on student learning outcomes at SMP Negeri 4 Medan.